Demographic and Contextual Predictors of Mental Health Outcomes among Indonesian Doctoral Students: A Cross-Sectional Study - Juliana Irmayanti Saragih; Fitri Andriani; Hari Basuki Notobroto (AL-ISHLAH: Jurnal Pendidikan, 2025)
Doctoral students face unique academic, financial, and social pressures that increase their risk of mental health problems. While global data suggest high rates of depression, anxiety, and stress among Ph.D. candidates, no systematic investigation has been conducted in the Indonesian context. This cross-sectional study assessed the mental health of 245 Indonesian doctoral students using the Depression Anxiety Stress Scales-21 (DASS-21). Data were collected via an online questionnaire and analyzed using chi-square tests and multinomial logistic regression to identify demographic and contextual predictors of mental distress. Findings revealed high prevalence rates: 47.8% reported moderate to very severe depression, 59.2% reported anxiety, and 47.3% experienced stress—exceeding global averages. Gender was the strongest predictor; women were significantly more likely to experience all three symptoms (p .001). Marital status and living arrangements were also significant, with married students and those living with family reporting better outcomes. Students employed while studying reported lower distress across all dimensions than full-time students. Field of study and stage of study were associated with mental health in bivariate analyses but lost significance in multivariate models, indicating confounding effects. The findings suggest that demographic and contextual factors such as gender, social support, and work-study balance significantly influence doctoral students’ mental health. Given the high prevalence of distress, institutions should prioritize targeted support systems, especially for women and full-time students. This study provides essential baseline data for policy and intervention development in Indonesian higher education.